Associative and Dissociative Social Interaction of Students of SMAN 1 Anjir Muara - Muhammad Yurbani; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah; Mutiani Mutiani; Jumriani Jumriani (Universitas Lambung Mangkurat, 2023)
The social interactions that occur at SMAN 1 Anjir Muara are divided into two, namely associative and dissociative interactions. Interactions that are associative generally occur because of the positive impact of teachers and students, for example when activities are carried out by the school, students participate in helping and participating in these activities. Dissociative interactions and interview guide. The research results are related to social interaction which is one of the processes in communicating and socializing between individuals and groups. The social interactions that occur at SMAN 1 Anjir Muara are divided into two, namely associative and dissociative interactions. Interactions that are associative generally occur because of the positive impact of teachers and students, for example when activities are carried out by the school, students participate in helping and participating in these activities. Dissociative interactions and interview guide. The research results are related to social interaction which is one of the processes in communicating and socializing between individuals and groups. The social interactions that occur at SMAN 1 Anjir Muara are divided into two, namely associative and dissociative interactions. Interactions that are associative generally occur because of the positive impact of teachers and students, for example when activities are carried out by the school, students participate in helping and participating in these activities. Dissociative interactions The social interactions that occur at SMAN 1 Anjir Muara are divided into two, namely associative and dissociative interactions. Interactions that are associative generally occur because of the positive impact of teachers and students, for example when activities are carried out by the school, students participate in helping and participating in these activities. Dissociative interactions The social interactions that occur at SMAN 1 Anjir Muara are divided into two, namely associative and dissociative interactions. Interactions that are associative generally occur because of the positive impact of teachers and students, for example when activities are carried out by the school, students participate in helping and participating in these activities. Dissociative interactionsis a process of resistance carried out by individuals and groups in the social process between them in society. Forms of dissociative processes are competition, competition, and conflict. Dissociative processes can be found in every society, although their form and direction are determined by the culture and social system of the society concerned.